Conventional and unconventional citizenship and its relationship with political self-efficacy in Chilean adolescents - Benavente, Luna (2023)
The crisis of political representation in Chile has led to a decrease in the participation of young people in elections, while increasing in social movements. These could affect how they perceive their ability to effect change through politics. This cross-sectional study analyzes, through self-report scales, gender differences in the relationship between internal political efficacy and the importance given to conventional and non-conventional political participation in a sample of Chilean adolescents (N = 949). Results show that the importance given to conventional politics is associated with internal political efficacy for men and women, while the importance given to unconventional politics is only associated for women. The importance of different forms of political participation in the formation of young political citizens is discussed, in the context of feminist mobilizations.